2011
DOI: 10.3892/ijmm.2011.805
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Re lowers blood glucose and lipid levels via activation of AMP-activated protein kinase in HepG2 cells and high-fat diet fed mice

Abstract: Abstract. Ginsenoside Re is a protopanaxatriol-type saponin isolated from Panax ginseng berry. Although anti-diabetic and anti-hyperlipidemic effects of Re have been reported by several groups, its mechanism of action is largely unknown until now. Here, we examine anti-diabetic and anti-hyperlipidemic activities of Re and action mechanism(s) in human HepG2 hepatocytes and high-fat diet fed C57BL/6J mice. Re suppresses the hepatic glucose production via induction of orphan nuclear receptor small heterodimer par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…One of the most efficient ways to modulate glucose metabolism in diabetic patients would be a perturbation on hepatic glucose production. Recently, ginsenoside Rb 2 , Re and Rg 1 were reported to suppress the hepatic gluconeogenesis in H4IIE and HepG2 cells, respectively, via activation of AMP-activated protein kinase (AMPK) [41,49,50].…”
Section: Anti-diabetic Activity and Action Mechsnisms Of Ginsengmentioning
confidence: 99%
“…One of the most efficient ways to modulate glucose metabolism in diabetic patients would be a perturbation on hepatic glucose production. Recently, ginsenoside Rb 2 , Re and Rg 1 were reported to suppress the hepatic gluconeogenesis in H4IIE and HepG2 cells, respectively, via activation of AMP-activated protein kinase (AMPK) [41,49,50].…”
Section: Anti-diabetic Activity and Action Mechsnisms Of Ginsengmentioning
confidence: 99%
“…In another related study, the same group revealed ginsenoisde Re to lower blood glucose and lipid level via activation of AMPK pathway in HepG2 cells and high-fat diet fed mice, suggesting therapeutic benefits on type 2 diabetic patients with insulin resistance and dyslipidemia [70]. …”
Section: Protective Effect Of Ginseng Extracts and Ginsenoisdes Onmentioning
confidence: 99%
“…It has been used widely as a tonic for various disorders in China, Korea and Japan for over two thousand years and is now a popular herbal remedy worldwide. Ginsenosides, the bioactive ingredients of ginseng, have been proven to provide therapeutic effects affecting the cardiovascular, endocrine, immune, and central nervous systems [6,7,8,9]. Ginsenosides are generally classified into two categories, namely the panaxadiols and the panaxatriols.…”
Section: Introductionmentioning
confidence: 99%